“I learned that sports teaches rape culture”: Assessing Sexual Violence Prevention Education for Intercollegiate Athletes - McCray, Kristy; Taylor, Elizabeth (Journal of Intercollegiate Sport, 2021)
In fall 2018, 81 intercollegiate athletes participated in Fair Play: Sexual Violence Prevention for Athletes. This study aimed to assess the efficacy of the Fair Play curriculum and facilitation, specifically learning if athletes’ attitudes toward women and/or rape myth acceptance changed as a result of their participation in Fair Play. Athletes completed pre- and post-test surveys to measure perceptions of sexual assault/rape myth acceptance (Gerger, Kley, Bohner, & Siebler, 2007) and gender roles (Spence, Helmreich, & Stapp, 1973). In addition, 20 athletes participated in semi-structured qualitative interviews to further explain their knowledge of sexual violence after completing Fair Play. Survey results showed significant differences for pre- and post-test scores on rape myth acceptance, but not for attitudes toward women. Interview results showed that Fair Play participants could articulate a raised awareness of sexual violence, appropriately define sexual violence and consent, and a rejection of rape myths. Implications include further understanding of effective rape prevention education.